Profile of the Availability and Use of Learning Media that Supports Improving Numeracy Skills in Elementary and Junior High Schools - Herman Syafri (Universitas Pendidikan Indonesia (UPI), 2024)
This research aims to determine the profile of the availability of learning media that supports improving numeracy skills in elementary and junior high schools in Tasikmalaya Regency and City and their use, using a qualitative approach, while the methods used are interviews and commentary studies. The research findings obtained are that several elementary schools and junior high schools in Tasikmalaya Regency and City have learning media that supports improving students' numeracy skills, the source comes from grants, schools rarely budget for purchasing media, and rarely even make their own media. However, unfortunately the existing media does not work optimally, because teachers are reluctant to use media and focus only on textbooks, even though all the sources interviewed said that the use of media in learning, especially in learning Mathematics, is very important.